Bringing Intercultural Perspectives into General EFL Learning during Covid-19: Some Insights - Muhammad Jauhari Sofi (Universitas Islam Negeri (UIN) Mataram, 2022)
Studies on intercultural language learning have revolved around the descriptive report of cultural facts, adjustment to the target language's culture, and cross-cultural do's and don'ts. They have not yet exposed the issue in much detail, especially in an emergency situation. This study aims to investigate practical ideas on how to engage Indonesian Islamic higher education students with intercultural perspectives during the Covid-19 pandemic. It addresses what the teachers think about interculturality in the general EFL learning and how they accommodate intercultural perspectives during the virtual class. Using a narrative inquiry, the data were collected through semi-structured interviews and observations. The researcher employed thematic analysis and theoretical lenses on interculturality-based language learning. The study showed that interculturality in EFL learning was not only unavoidable but also indispensable. This learning suggested an equal position between teachers and students in terms of authority of knowledge and vocal participation. The teachers also accommodated the core principles of intercultural perspectives in general EFL learning through proactive construction, connection-making, social interaction, reflection, and commitment, even though they did not take place optimally during virtual learning. Here, the students engaged with one another to exchange information, link ideas, and make sense of meanings. The overall findings of this study imply the vital role of teachers in helping students recognize, appreciate, and respond to cultural variety during the virtual learning process.